2021
DOI: 10.1097/jnc.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Social and Structural Barriers to Primary Care Access Among Women Living With HIV in Metro Vancouver, Canada: A Longitudinal Cohort Study

Abstract: This study examines correlates of being unable to access primary care in the past 6 months among cisgender (cis) and trans women living with HIV (WLWH). Data were drawn from a longitudinal community-based cohort study of WLWH (ages 141) in Metro Vancouver, Canada (2014Canada ( -2017. Of 291 participants contributing 914 observations, 15.5% reported being unable to access primary care at baseline. In multivariable analysis, increased odds of being unable to access primary care was associated with (a) having im/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The frequent use of criminalized drugs for pain management indicates that many WLWH may have difficulty accessing pain care. A previous examination of barriers to primary care in our study context concluded that equity-oriented approaches may improve access for WLWH [ 19 ]. The EQUIP framework, which operationalizes 4 dimensions of equity-oriented care (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequent use of criminalized drugs for pain management indicates that many WLWH may have difficulty accessing pain care. A previous examination of barriers to primary care in our study context concluded that equity-oriented approaches may improve access for WLWH [ 19 ]. The EQUIP framework, which operationalizes 4 dimensions of equity-oriented care (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previously identified psychological correlates of pain in PLWH include anxiety, depression, post-traumatic stress, and substance use disorder [ 20 , 30 , 53 , 67 ]. Sociostructural correlates of pain in PLWH are less well characterized despite evidence that social interactions modulate the experience of pain [ 34 ] and structural inequities among PLWH limit access to care [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women living with HIV (WLWH) account for 18% of all people living with HIV (PLWH) in British Columbia, 1 Canada, and continue to experience unique and substantial barriers to accessing necessary health care. [2][3][4][5][6][7] WLWH can experience suboptimal and stigmatizing interactions with health care services providers by way of provision of substandard treatment, denial of health care services, excessive/unnecessary precautions taken by health care services staff, and non-consensual disclosure of patient's HIV status. [7][8][9] Discrimination and marginalization in accessing care can lead to decreased utilization of health saving services, 10,11 increased mental health issues, and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing colonial violence and gender-based violence continues to impact the health and well-being of Indigenous women, Two-Spirt Peoples, sex workers, and women living with HIV ( 2 – 6 ). Historical and ongoing colonial violence has impacted Indigenous health and Indigenous women Two-Spirit Peoples, women living with HIV, and sex workers face multiple barriers to accessing reliable healthcare services ( 7 ) and people with marginalized and minoritized gender identities face increased barriers to accessing healthcare on the ancestral, occupied territories of the Musqueam, Squamish, and Tsleil-Waututh Peoples in what is now referred to as Vancouver ( 8 , 9 ). Barriers that impact health access are rooted in racism and discrimination.…”
Section: Introductionmentioning
confidence: 99%